2021
DOI: 10.3390/ijerph19010235
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Exposure and Malignant Mesothelioma in Construction Workers—Epidemiological Remarks by the Italian National Mesothelioma Registry (ReNaM)

Abstract: Notwithstanding the ban in 1992, asbestos exposure for workers in the construction sector in Italy remains a concern. The purpose of this study is to describe the characteristics of malignant mesothelioma (MM) cases recorded by the Italian registry (ReNaM) among construction workers. Incident mesothelioma cases with a definite asbestos exposure have been analyzed. Characteristics of cases and territorial clusters of crude rates of MM in construction workers have been described, as well as the relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Our results are in line with a previous study focusing on asbestos removal workers in Great Britain, which found a high number of deaths for all cancer including, among others, mesothelioma (Frost et al ., 2008). A recent analysis of the Italian National Mesothelioma Registry reported 3574 incident cases of mesothelioma in construction workers in the 1993–2018 period with an increasing trend over time and a mean latency of 20.9 years and based on economic activity coding about 1.1% of recorded exposure periods were attributable to asbestos removal and disposal firms (Binazzi et al ., 2022). It is plausible that at the next follow-up, the number of workers found in the link between SIREP exposure data and ISTAT mortality archives will increase, also in consideration of the long latency of asbestos-related diseases and especially for malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with a previous study focusing on asbestos removal workers in Great Britain, which found a high number of deaths for all cancer including, among others, mesothelioma (Frost et al ., 2008). A recent analysis of the Italian National Mesothelioma Registry reported 3574 incident cases of mesothelioma in construction workers in the 1993–2018 period with an increasing trend over time and a mean latency of 20.9 years and based on economic activity coding about 1.1% of recorded exposure periods were attributable to asbestos removal and disposal firms (Binazzi et al ., 2022). It is plausible that at the next follow-up, the number of workers found in the link between SIREP exposure data and ISTAT mortality archives will increase, also in consideration of the long latency of asbestos-related diseases and especially for malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant mesothelioma is a rare malignancy with an estimated global incidence of 0.30 cases per 100,000 inhabitants in 2020 [ 6 ]. And among a variety of plausible causes, asbestos exposure is widely considered the main risk factor as it is reported that up to 90% of MPM in men in Europe and North America are attributable to asbestos exposure [ 1 - 6 ]. The latency interval from the initial causal exposure to the development of the disease varies from 20 to 40 years [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described that a bad prognosis is also associated with weak performance status, being male, high white blood cell count, chest wall pain, and the sarcomatoid histological type [ 8 ]. Many countries have tried long ago to either ban or control the use of asbestos as awareness increased about its risk in developing malignancies [ 2 , 6 , 11 ]. However, malignant mesothelioma is considered a world health issue, not only due to its poor prognosis but also due to its increasing incidence despite the wide regulatory actions taken to decrease its use [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy (decree 308/2002) a national MM registry (Registro Nazionale Mesoteliomi, National Mesothelioma Registry, ReNaM) has been formally established (although some regions had already started registration in the 1990s). ReNaM recorded more than 30 000 MM cases in the period 1993–2018 10. Construction is among the industries with the largest asbestos use in the past and is paying the largest toll: of 17 191 cases with occupational exposure, 3574 MM cases (20.8%), almost all men, had been exposed in the construction industry 10…”
Section: Introductionmentioning
confidence: 99%